Vaccination pain and anxiety reduction: Integrative literature review (Research, Society and Development, 2021)
Vaccination is essential for the immunological protection of individuals, especially in their first years of life. We can say that vaccines are effective in preventing diseases, by reducing vaccine-preventable diseases in the world. The aim of this study is to address strategies for reducing pain and fear of vaccines in patients. This is an integrative literature review, including data collection through bibliographic surveys to identify productions on pain management during vaccination. For the development of this review, the 05 phases of the process of elaborating an integrative review and the searches carried out in the Virtual Health Library (VHL) and PubMed were presented. Use of local anesthetics, cryotherapy, music therapy, use of therapeutic toys, breastfeeding and parental participation were some of the strategies detected. Vaccination is one of the most beneficial health interventions to save lives. It is up to health professionals to seek strategies to ensure quality care, providing qualified care throughout the vaccination process. The nurse must also be aware of the signs of anxiety presented by the patient, as well as maintain an adequate posture to handle the situation. Therefore, it is necessary that the professional has knowledge and creativity throughout the vaccine administration process, ensuring comprehensive care, with a single and exclusive focus on the patient.